Differentiated Learning Instruction in the Cultural Studies Classroom: EFL Students’ Experiences - Aziz, Kris Inayah Hasnia; Andanty, Ferra Dian (Journal of English for Academic and Specific Purposes (JEASP), 2024)
Learning experience particularly performed by students. Learning outcomes influenced by students’ learning experience.  This study aims to explore EFL students’ experiences through differentiated learning instruction, which focuses on readiness, interest, and learning environment aspects in the Cultural Studies classroom. This research applied the qualitative method with a narrative inquiry approach. To collect the data, the researcher used a semi-structured interview to consider the narration of English Language Education 6th semester in English Language Education Department at Universitas PGRI Adi Buana Surabaya. The results of the study showed that some EFL students experiences by using differentiated learning instruction improved their readiness in having self-esteem for their knowledge and English language skills, improved their interest in the form of students’ attitude and teacher’s roles, and learning environment by showing their comfortable situation in expressing opinions in discussion. Furthermore, the study found that there were several impacts by using differentiated learning instruction for EFL students. This study recommended for the students to help each other in the learning process. In addition, the researcher also suggested the teacher to overcome student’s problems or what the student’s needs by using differentiated learning instruction.